Pemberdayaan Masyarakat Melalui Penyuluhan Upaya Peningkatan Kesehatan Reproduksi Melalui Perilaku Hygiene Genitalia Di Smk Swasta Bharlind Tahun 2021 - Sari Rahma Fitri; Suriati Lubis (Journal of Community Development, 2021)
Self-care is performed as one of the efforts to improve health. Genital personal hygiene problems arise because of neglected hygiene problems. Reproductive health can be achieved one of them by doing personal hygiene genitalia in women to keep it clean and healthy. The importance of maintaining personal hygiene genatalia to avoid the appearance of disorders in the reproductive organs.The subjects in the service activity were 55 teenage students at SMK Swasta Bharlind, which was held on Thursday, October 7, 2021. This activity was carried out using the counseling method. Community service activities received a good response from all teenage students. When the activity began, teenage students of SMK Swasta Bharlind were gathered in the yard, then socialized counseling material on genital hygiene behavior, and asked questions to teenagers. In the delivery of the material, it turns out that many adolescents do not understand about the personal hygiene of their respective genital hygiene. After this service activity is carried out, it is hoped that teenage students will be able to apply or apply in their daily lives and minimize genital hygiene problems.